4A.01: LONG-TERM EFFECTS OF RENAL ARTERY DENERVATION IN REAL WORLD PATIENTS WITH UNCONTROLLED HYPERTENSION FROM THE GLOBAL SYMPLICITY REGISTRY. (June 2015) - Mancia, G.; Mahfoud, F.; Narkiewicz, K.; Ruilope, L.M.; Schlaich, M. P.; Schmieder, R.E.; Williams, B.; Böhm, M.
Abstract : Objective: The Global SYMPLICITY Registry (GSR) provides real world experience regarding the effects of radiofrequency denervation of the renal artery nerves in patients with uncontrolled hypertension. These data in hypertensive patients with a high proportion of concomitant conditions also characterized by sympathetic nervous system will further characterize the effects of renal denervation across a diverse patient population. Design and method: The GSR is a prospective, open-label, registry being conducted at 245 international sites. Office and 24-hour ambulatory blood pressure (BP) change, laboratory values and protocol-defined safety events are collected. One year results in the first 1000 enrolled patients are now available and two-year results in 600 patients will be available in the spring for presentation. Results: In the first 1000 consecutive patients enrolled, the mean age was 61 ± 12 years, 61% were male and mean body mass index was 30 ± 6 kg/m2. Comorbidities included diabetes mellitus (42%), renal dysfunction (estimated glomerular filtration rate [eGFR] <60 ml/min/1.73m2; 23%), obstructive sleep apnea (11%) and history of cardiac disease (51%). Baseline office BP was 165/89 ± 24/16 mm Hg and baseline 24-hour BP was 154/86  ± 18/14 mm Hg. 1 year office systolic BP change in 740 patients was -13.0 ± 26.3 mmHg (p < 0.001) and 24-hr systolic BP change (n = 390) was -8.3 ± 17.8 mmHg (p < 0.001). In patients with more severe hypertension (baseline office systolic blood pressure of at least 160 mm Hg plus an ambulatory 24-hour systolic blood pressure at least 135 mm Hg while taking 3 or more antihypertensive medications) the office systolic BP change was -21.5 ± 25.6 mmHg (p < 0.001) and the 24-hr systolic BP change was -11.4 ± 17.9 mmHg (p < 0.001). At 1 year post-denervation there were 7 cardiovascular deaths, new renal artery stenosis >70% occurred in 2 patients, and new onset end-stage renal disease occurred in 3 patients. Conclusions: Renal denervation in a large real world population resulted in significant blood pressure reductions 1 year post-procedure. There were no long-term safety concerns following the denervation procedure. These data, including analysis of the BP-lowering effects of RDN in select subgroups, will be updated with two year follow-up of approximately 600 patients in June.